The bride experiment : what happens when single women get fed up? - Jefferson, Mimi. (Deer Park, NY : Urban Christian/Urban Books ; East Rutherford, NJ : Distributed by Kensington Corp., 2011)
While picking up the pieces of his shattered life, James, a self-proclaimed womanizer, is introduced to Pastor Benjamin, who shows him a world he did not know existed--one filled with single men who love God intensely, abstain from sex until marriage and treat women like gold.
Includes reader's guide questions.
Keywords: African American single people -- Fiction; Christian life -- Fiction; Christian fiction; Urban fiction